2012
DOI: 10.1007/s10725-012-9682-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation and secondary product production by Merwilla plumbea (Lindl.) Speta

Abstract: Merwilla plumbea is a popular but threatened traditional medicinal plant sold at herbal markets in South Africa. It produces bioactive compounds and contributes to Traditional African Medical systems for the treatment of various diseases. Due to high demand, the plant is recommended for commercial cultivation. We investigated in vitro propagation and secondary compound production in in vitro cultures of M. plumbea, cultivated on Murashige and Skoog (Physiol Plant 15:473-497, 1962) medium supplemented with vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…The root tissues, which contain minor quantity of WA, did not show any significant variations between in vitro, green house and field grown plants, however, roots of green house plants showed slightly higher accumulation (0.835±0.15 mg/ g DW) (Table 2 and 3). The bioactive content in the present study was thus varied and tissue dependent probably due to the de novo synthesis as reported in the previous studies (Sangwan et al 2007a, b;Baskaran and Jayabalan 2008;Dewir et al 2010;Baskaran et al 2012Baskaran et al , 2013. Dynamics of WA in the in-vitro roots were also investigated in the liquid medium containing 2.0 μM of IBA.…”
Section: Rooting Of Shoots and Acclimatization Ex Vitrosupporting
confidence: 60%
See 1 more Smart Citation
“…The root tissues, which contain minor quantity of WA, did not show any significant variations between in vitro, green house and field grown plants, however, roots of green house plants showed slightly higher accumulation (0.835±0.15 mg/ g DW) (Table 2 and 3). The bioactive content in the present study was thus varied and tissue dependent probably due to the de novo synthesis as reported in the previous studies (Sangwan et al 2007a, b;Baskaran and Jayabalan 2008;Dewir et al 2010;Baskaran et al 2012Baskaran et al , 2013. Dynamics of WA in the in-vitro roots were also investigated in the liquid medium containing 2.0 μM of IBA.…”
Section: Rooting Of Shoots and Acclimatization Ex Vitrosupporting
confidence: 60%
“…Cytokinins are a class of plant growth substances that are active in promoting cell division as well as being active in numerous physiological processes, including plant cell growth and differentiation (Mahesh and Jeyachandran, 2013). The stimulating effect of BA alone or in combination with Kn on bud breaking and in vitro multiple shoot formation has been reported in W. somnifera (Ray and Jha, 2001;Sharada et al 2007;Ahuja et al 2009;Dewir et al 2010;Mir et al 2014a), Trichodesma indicum (Mahesh and Jeyachandran, 2013) and Drimia robusta (Baskaran et al 2013) and many other species (Kumar et al 2005;Baskaran et al 2012;Thiem et al 2013). The positive effect of BA was observed only unto a threshold of 5.0 μM as the further increase in the concentration of BA alone or in combination with Kn did not elicit any greater response in the parameters studied.…”
Section: Shoot Proliferation and Establishmentmentioning
confidence: 99%
“…Growth regulators have been used in agriculture for decades, but little is known regarding the effects of these compounds on the production of secondary metabolites [3,9,22,28]. In the present study, addition of BAP to the BM used for micropropagation of M. piperita effectively increased plant growth and EO production without altering EO composition.…”
Section: Discussionmentioning
confidence: 63%
“…Chemical changes were noted in some cases but not in others. In view of the fact that growth regulators influence plant growth and development through their effects on physiological and biochemical processes and even gene regulation, there are a great number of ways in which application of these compounds may alter secondary metabolite production [14,21,22]. Growth regulators can influence EO biosynthesis and the formation and development of storage structures.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, quercetin may aid in the prevention of certain diseases, such as cancer, atherosclerosis, and chronic inflammation [27] . A previous study reported that eighteen polyphenols were identified from extracts of the aerial and underground parts of S. bifolia (caftaric acid, isoquercitin, routine, myricetol, fistein, quercetol, patuletin, gentisic acid, caffeic acid, chlorogenic acid, p-coumaric acid, ferulic acid, hyperoside, quercitrin, luteolin, kaempferol, apigenin and sinapic acid) [28] .…”
Section: Resultsmentioning
confidence: 99%